Increased Dryland Winter Wheat Yields by Nitrogen Fertilizer Topdressing and its Relationship to Soil Moisture, Available N, P and K in Northwestern China. Issue 5 (8th March 2016) - Zhao, Hu-Bing; Wang, Zhao-Hui; Xue, Cheng; Huang, Dong-Lin; Malhi, Sukhdev S.
ABSTRACT: Winter wheat (Triticum aestivum L.) production in northwestern China as a monoculture is hampered by unfertile soil and drought. With the fast-developing Chinese chemical fertilizer industry, many farmers now use more nitrogen (N) fertilizer as topdressing for winter wheat in early spring, in addition to a basal dose of N fertilizer applied in the previous autumn at seeding time. The objective of this study was to evaluate the increase in grain yield of dryland winter wheat by early spring N fertilizer topdressing, and its relationship to soil moisture, available N, phosphorus (P) and potassium (K). Field experiments with no N fertilizer topdressing (Fb ) and N fertilizer topdressing (Fb+t ) treatments were carried out over two growing seasons at 54 site-years to assess the relationship between increase in winter wheat grain yield by early spring N fertilizer topdressing and soil moisture, available N, P and K in Changwu county, Shaanxi province, China. Compared to Fb treatment, the Fb+t treatment produced grain yields lower at 10 site-years, and increased by <10% at 21 site-years and by >10% at 23 site-years. The results indicated that topdressing N fertilizer could increase wheat grain yield when soil nitrate-N accumulation in the 0–20, 20–40 and 40–60 cm depths was less than 121.7, 36.4 and 24.1 kg N ha −1, and soil moisture content in the 40–60, 60–80 and 80–100 cm depths was more than 15.7%, 16.7% and 16.9%, respectively. The findings also suggested that it is not necessary to analyze soil for ammonium-N, available P and K before topdressing N fertilizer. It is necessary to analyze 0–60 cm soil profile for nitrate-N and 40–100 cm depth for soil moisture before topdressing N fertilizer for winter wheat in dryland areas of northwestern China.